SPIRITUALITAS INTERKULTURAL: BERSELANCAR DALAM ERA DIALOG ANTARPERADABAN - Raymundus Sudhiarsa (Studia Philosophica et Theologica, 2009)
Conditions of religious pluralism are on the increase everywhere. Everybody is coming face to face with believers of other faiths. Those who are not sufficiently equipped with regard to the history and nature of other religions or religious traditions will find themselves in difficulty to interact with ‘the others’. Intolerances, conflicts, and violences of all kinds, which are fundamentaly evil, are just ‘understandable consequences’ that occur throughout our human history. This article tries to offer some insights regarding the struggles of the Christians to comprehend their own position among believers of other faiths and to accept others as partners of dialogue on their way to live out their inner being as Imago Dei and to build up a more humane society, namely a world of friendship and love. Today’s era of dialogue of civilization is actually a great challenge and fertile times for Christians as the pilgrim Church to intensifly develop their spirituality which is intercultural by nature